Influencing Factors of Disturbance Effects of Blasting and Driving of Deep Mine Roadway Groups - Jiaguang Kan; Peng Wang; Peng Wang (Shock and Vibration)
The development and application of roadway group layout methods in coal mines have become more common and the mutual disturbance of blasting and driving of roadway groups has also become more prominent at depth. To improve the stability of rock mass surrounding roadways, we performed a systematic study on the factors that influence blasting and driving disturbances of adjacent roadways in deep mine roadway groups. We use the dynamic analysis module in FLAC3D to obtain the influence laws of three factors on the disturbance effects of adjacent roadways, namely, excavation methods, layer position changes of the roadway group, and whether or not bolt support is applied in the first roadway. Blasting strongly influences the surrounding roadway and increased horizontal distance can effectively reduce the disturbance effects of blasting and driving between adjacent roadways compared with increased vertical distance. Bolt support of the first excavated roadway enhances the roadway integrity and better stabilizes the rock structure surrounding the roadway. Industrial tests were carried out on three uphill roadways in the Gubei no. 1 mine (6-2). The monitoring results show that the movement of the roof and floor of the floor uphill return wind roadway is larger than that on the two sides. There is no notable change in the deformation speed of the surrounding rock in the floor return air roadway, but the deformation speed of the uphill conveyor belt roadway changes significantly. The results show that when the blasting excavation of a deep mine roadway group is more than five times the tunnel spacing, the increased horizontal distance effectively reduces the disturbance effects of excavation between adjacent roadways, which is consistent with the simulation results.